Schools’ Research Operations, Planning and Development: Bases for Policy Enhancement - Pabiona, Dayle P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study was conducted to determine the schools’ research operations, planning, and development as bases for policy enhancement in the Schools Division of Iloilo for school year 2023-2024. The independent variables included age, sex, length of service, educational attainment, and congressional district, while the dependent variables were schools’ operations, planning, and research development. A total of 385 elementary teachers were selected using Slovin’s formula, and data were collected through a researcher-made questionnaire. Statistical analyses, including frequency count, percentage, mean, t-test, One-way ANOVA, and Pearson’s r, were employed to interpret the results. Findings indicated that most respondents were young, predominantly female, with substantial lengths of service. Most had a bachelor's degree and across various congressional districts, with the Second Congressional District having the highest representation. The study revealed that teachers rated the level of schools’ research operations as high, research planning as very high, and research development as high. No significant differences were found in assessments based on the teachers' profiles. However, a strong positive correlation was noted between research operations and planning, as well as between planning and development, while the relationship between operations and development was weak and non-significant. These findings underscore the need for policy enhancements that foster collaboration and resource allocation in educational research, ultimately contributing to more effective teaching practices and improved learner outcomes. Implementing targeted policies that address identified gaps can empower teachers and strengthen the overall research framework within schools.